1997
DOI: 10.1111/j.1399-0004.1997.tb02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies exclude the AT‐V gene(s) from the translocation breakpoints in an AT‐V patient

Abstract: An 8‐year‐old girl with severe microcephaly of prenatal onset, borderline intelligence, defects of skin pigmentation, deficiency of both humoral and cellular immunity, a normal serum α‐fetoprotein level and hypersensitivity to ionizing irradiation is described. Spontaneous chromosomal breakage in lymphocytes together with the clinical presentation led to the diagnosis of ataxia telangiectasia variant (AT‐V). In addition, the patient carried a constitutional translocation of paternal origin: 46,XX,t(3;7)(q12;q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Four patients presented with disseminated disease at diagnosis and in fi ve patients the tumor was large (T3-T4 according to the Chang staging system) (Chang et al 1969 ) . None of the four patients who underwent irradiation experienced radiotherapy-related serious adverse events, suggesting that irradiation in NBN heterozygotes is well tolerated, in contrast to the biallelic mutation carriers (Bakhshi et al 2003 ;Chrzanowska et al 1997 ;Distel et al 2003 ) . One patient was retreated at relapse with radiotherapy with no unexpected reactions.…”
Section: The Contribution Of Nbnmentioning
confidence: 76%
See 2 more Smart Citations
“…Four patients presented with disseminated disease at diagnosis and in fi ve patients the tumor was large (T3-T4 according to the Chang staging system) (Chang et al 1969 ) . None of the four patients who underwent irradiation experienced radiotherapy-related serious adverse events, suggesting that irradiation in NBN heterozygotes is well tolerated, in contrast to the biallelic mutation carriers (Bakhshi et al 2003 ;Chrzanowska et al 1997 ;Distel et al 2003 ) . One patient was retreated at relapse with radiotherapy with no unexpected reactions.…”
Section: The Contribution Of Nbnmentioning
confidence: 76%
“…Tzortzatou-Stathopoulou, personal communication, 2002). In four of these fi ve children, the founder mutation, c.657del5, was identi fi ed on both alleles (Chrzanowska et al 1997 ;Distel et al 2003 ; and two further cases of Slavic origin, unpublished), and one patient was a compound heterozygote of the mutation c.657del5 in exon 6 and the mutation c.1142delC in exon 10 (Distel et al 2003 ) . Radiotherapyrelated death was documented in three children.…”
Section: The Contribution Of Nbnmentioning
confidence: 94%
See 1 more Smart Citation
“…Brain tumours such as medulloblastoma [65][66][67], and rhabdomyosarcoma of extremely rare perianal localization have been reported to develop more frequently in NBS patients [24,31,44,61,63]. Single cases of papillary thyroid carcinoma, gonadoblastoma, glioma, meningioma, neuroblastoma, and Ewing sarcoma were also described [48].…”
Section: Predisposition To Malignanciesmentioning
confidence: 99%
“…Brain tumours in these patients have been described (medulloblastoma, glioma). Treatment of such patients should be restricted to chemotherapy only as it was reported that CNS irradiation resulted in radiotherapy-related death in 3 NBS patients [65][66][67].…”
Section: Assessment Care and Treatment Of Malignancymentioning
confidence: 99%